Tourists and Buddhist heritage sites: An integrative analysis of visitors' experience and happiness through positive psychology constructs. (December 2019) - Huang, Keji; Pearce, Philip L; Wu, Mao-Ying; Wang, Xiong-Zhi
The influence of visiting Buddhist heritage sites on happiness is the core concern of this article. China's four sacred Buddhist mountains provided the setting for the study. Sixty semi-structured interviews were conducted to examine the positive effects of Buddhism on visitors. Thematic analysis was first undertaken to understand the Buddhism-induced happiness. In the terms of Buddhism, the visitors' happiness was related to the law of karma, impermanence and reincarnation. The PERMA model from positive psychology was then utilized as a second interpretive framework, in which positive changes in visitors' attitudes, behaviours and life were noted. The links between the core values of Buddhism and the PERMA model were then established and portrayed. The study makes a theoretical contribution by connecting the positive psychology constructs and the effects of Buddhism in the tourism context. In addition, this study provides insightful suggestions for local communities to manage religious heritage sites sustainably.